The MiBlend Randomized Trial: Investigating Genetic Polymorphisms in Personalized Responses to Fruit and Vegetable Interventions for Chronic Disease Prevention - Julia N. DeBenedictis; Na Xu; Theo M. de Kok; Simone G. van Breda (Antioxidants)
Background: The MiBlend Study investigated the effect of consuming different combinations of fruits and vegetables (F&Vs) blends on markers of chronic disease risk and gene expression changes in healthy human subjects. Overall, the increase in F&Vs led to reduced susceptibility to the induction of DNA damage ex vivo, higher antioxidant capacity of plasma, and improved microvasculature as reflected by retinal analysis. As with most dietary intervention studies, inter-individual variability was observed in the responses, which might be the consequence of genetic differences. Therefore, this study aims to identify if genetic variants in relevant genes affect outcomes and responses to the dietary interventions. Methods: The literature review identified 15 polymorphic genes related to phytochemical metabolism, oxidative stress, and detoxification, which were tested in 146 participant samples using TaqMan and PCR analysis. The effect of genotypes on study outcomes was determined via analysis of variance. Results: XRCC1 wildtype carriers were more protected from ex vivo-induced DNA damage after consuming flavanol-rich F&Vs than other variants. XRCC1 is involved in DNA repair, particularly oxidative damage, and its wildtype allele enhances repair efficiency. GSTP1 wildtype carriers had a larger improvement in microvasculature after all F&V blends, especially those rich in polyphenols. GSTP1 polymorphisms likely affect microvascular responses to polyphenol-rich F&V intake by modulating detoxification and fiber-derived butyrate that can influence arterial dilation and endothelial function. Conclusions: Stratifying participants by relevant genetic polymorphisms can reveal predisposed responses to nutrients and guide efforts to personalize disease prevention strategies.